Aerosol‐Jet Printed Fillets for Well‐Formed Electrical Connections between Different Leveled Surfaces. Issue 11 (21st September 2017) - Gu, Yuan; Hines, Daniel R.; Yun, Victor; Antoniak, Michael; Das, Siddhartha
Abstract: As additive manufacture becomes more prevalent in the fabrication of advanced electronics, there is a need to create well‐formed, robust circuitization, and interconnects between components mounted onto different leveled surfaces (DLSs). Here, an algorithm is developed for aerosol‐jet printing of fillet structures that enable such a circuitization and hence a smooth electrical transition between the DLSs. The fillets are printed using an ultraviolet‐curable polymer ink in the presence of in situ curing. A specific deposition rate is established in order to ensure a precise architecture. Further, a surface smoothing technique is employed to smooth out the stepped surface topology of a fillet resulting from the layer‐by‐layer printing of in situ cured material. Finally, it is ascertained that the performance of these printed fillets is highly satisfactory by carrying out the resistance measurements of the conducting lines printed over these fillet structures both before and after temperature cycling and establishing the mechanical stability of the fillets by employing an adhesion test. This technology ensures that the fillets not only establish a mechanical integration/attachment of the two DLSs, but more importantly that they also provide a well‐formed surface onto which an electrical connection between these two DLSs can be established. Abstract : An algorithm for the aerosol‐jet printing of fillet structures is developed, which not only ensures a mechanical integration/attachment of the two different leveled surfaces (DLSs), but more importantly also provides a well‐formed surface for developing robust circuitization and electrical interconnection between components mounted onto the DLSs.